2016
DOI: 10.21276/ijmrp.2016.2.6.043
|View full text |Cite
|
Sign up to set email alerts
|

Knoweledge, Attitude and Practice among Women Toward Premenstrual Syndrome Attending Ministry of Health Primary Health Care Centers in Taif City, Saudi Arabia

Abstract: Background: Research on premenstrual syndrome (PMS) is generally lacking in the Gulf countries, a region with unique cultural features that might influence expectations and selfperception of the disease. Little, if any, is known about the knowledge and attitude among women in Taif toward PMS. The shortage of such data in the general female Saudi population, too, emphasizes this concept, and hence the need to research on it. Objectives: To study knowledge and attitude of woman attending PHCCs, MOH toward PMS as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…It is identified by the absence of menstrual cycles for 12 consecutive months, with no discernible medical or physiological causes [ 13 , 15 ]. The typical duration of menopause among Saudi women is approximately 49 years [ 39 ]. Regarding the knowledge of the study population, the findings of this study demonstrated a good understanding of the onset of menopause among Saudi women (Item 2 and Table 2 ), menstruation disorders (Item 3 and Table 2 ), and the influence of genetic background on menopause (Item 4 and Table 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is identified by the absence of menstrual cycles for 12 consecutive months, with no discernible medical or physiological causes [ 13 , 15 ]. The typical duration of menopause among Saudi women is approximately 49 years [ 39 ]. Regarding the knowledge of the study population, the findings of this study demonstrated a good understanding of the onset of menopause among Saudi women (Item 2 and Table 2 ), menstruation disorders (Item 3 and Table 2 ), and the influence of genetic background on menopause (Item 4 and Table 2 ).…”
Section: Discussionmentioning
confidence: 99%
“…Premenstrual syndrome (PMS) is a recurrent luteal phase condition characterized by physical, psychological, and behavioral changes that impair daily activities [1]. Common psychological symptoms include changes in mood, irritation, and depression, and frequently reported physical symptoms include breast tenderness, bloating, and headache [2].…”
Section: Introductionmentioning
confidence: 99%